Reconstructing Criminal Accountability of Children in Pornography Dissemination Cases: Case Study of Decision Number: 4/Pid.Sus-Anak/2024/PN Ktb - Wahid, Bahrul Alim (Reformasi Hukum, 2025)
Globalization and advances in information technology, particularly the internet, have brought various conveniences while also generating new problems, including the rise of cybercrime. One emerging phenomenon is the involvement of children as perpetrators of criminal offenses, including the dissemination of child pornography. This study aims to describe and analyze the criminal accountability of children in pornography dissemination cases based on Decision Number: 4/Pid.Sus-Anak/2024/PN Ktb, as an effort to reconstruct the understanding of criminal accountability of children in conflict with the law. This research employs a qualitative method with a doctrinal legal research approach. The focus of the study is on the criminal accountability of children in pornography dissemination cases through an examination of Law Number 44 of 2008 on Pornography and Law Number 11 of 2012 on the Juvenile Criminal Justice System. The data used are secondary data obtained through library research and analyzed descriptively. The findings indicate that the criminal accountability of children in the case was based on the fulfillment of the elements of Article 29 of Law Number 44 of 2008. The child offender, aged 15 years, was proven to have disseminated pornographic content through social media. The judge considered the child legally capable of being held accountable and imposed a sentence of one year of imprisonment and three months of job training.